PRE-FEASIBILITY STUDY FOR THE INSTALLATION OF A SMALL BUSINESS PROCESSING Nectars - Livia Alejandro, Marly Consuelo (1999)
This article demonstrates the feasibility of installing a small processing company Huaral nectars, checking that there is a potential market, recommending the most appropriate technology, and demonstrating their economic and financial viability.